Lost treasure of the Emerald Eye - Stilton, Gern̤imo. (New York : Scholastic, 2004)
When Geronimo's sister, Thea, discovers an old, mysterious map showing a secret treasure hidden on a faraway island, the gang of the "Rodent's gazette" is dragged into a treasure hunt.
RL3.
008-012.
530
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Treasure troves -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Buried treasure -- Fiction; Mystery and detective stories; Humorous stories; Newspapers -- Fiction; Adventure and adventurers -- Fiction